2008
DOI: 10.1039/b805324c
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3-Triazolyl-pyridine derivatives as chelating ligands for blue iridium(iii) complexes. Photophysics and electroluminescent devices

Abstract: We report on the study of a new family of neutral heteroleptic Ir(F 2 ppy) 2 L (F 2 ppy ¼ 2-(2,4-difluorophenyl)pyridine) complexes bearing different triazole derivatives (L ¼ 2-(1,2,3-triazol-5-yl)pyridine) as the third ligand. Two of these ligands were used for the first time as ancillary ligands in iridium(III) complexes. A full photophysical and electrochemical study of these complexes is reported here, together with theoretical investigations at the density functional theory (DFT) level. The complexes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 52 publications
6
71
0
2
Order By: Relevance
“…A triazolyl iridium complex with blue-emitting properties 248 Theranostic agents combine both diagnostic and therapeutic properties into one entity, and seeking to develop contrast agents for optoacoustic imaging, Franchini employed both copper and ruthenium catalyzed cycloadditions to link silver nanoparticles (NPs), derivatized with an alkyne unit, to lipophilic azide-functionalized gold nanorods (GNRs). 249 The cycloadducts were subsequently incorporated into PEG-based co-polymers to produce polymeric nanoparticles (PNPs).…”
Section: Figure 30mentioning
confidence: 99%
See 1 more Smart Citation
“…A triazolyl iridium complex with blue-emitting properties 248 Theranostic agents combine both diagnostic and therapeutic properties into one entity, and seeking to develop contrast agents for optoacoustic imaging, Franchini employed both copper and ruthenium catalyzed cycloadditions to link silver nanoparticles (NPs), derivatized with an alkyne unit, to lipophilic azide-functionalized gold nanorods (GNRs). 249 The cycloadducts were subsequently incorporated into PEG-based co-polymers to produce polymeric nanoparticles (PNPs).…”
Section: Figure 30mentioning
confidence: 99%
“…248 Metal complexes can be employed in light-emitting diodes (LEDs), acting as phosphorescent dopants and facilitating intersystem crossing from the singlet to the triplet excited state. The colours red, green and blue are all necessary for applications in color displays, and De Cola found that a complex prepared via RuAAC, using Cp*Ru(PPh 3 ) 2 Cl as the catalyst, displayed blue emission with high quantum yields (Fig.…”
Section: Devicesmentioning
confidence: 99%
“…The MLCT character was also distinguished by a broad and unstructured spectral shape of the phosphorescence spectrum, 7-9 whereas the ligand-centered (LC) transitions exhibited vibronic fine structures. [7][8][9][10] The PL spectrum at 300 K revealed another band at 537 nm. The energy of this band was ~1000 cm −1 lower than the peak at 509 nm, suggesting some overlap of the vibrational satellites.…”
mentioning
confidence: 99%
“…Compostos baseados em Ir(III) se destacam dos outros por apresentarem grande rendimento quântico, longos tempos de vida de luminescência (da ordem de μs, emissão do tripleto), uma grande gama de cores passíveis de serem emitidas, além de maior estabilidade térmica quando comparados com compostos baseados em outros metais [12][13][14][15] . Além disso, complexos de Ir(III) são eletroluminescentes, o que possibilita o seu uso não só em OLED's 16 , mas também em LEEC's 17 .…”
Section: Diodos Emissores De Luz Orgânicos (Do Inglês Organic Light-unclassified
“…Por estes motivos novos complexos de Ir(III) que emitam intensamente no azul vem sendo intensamente investigados 3,16,17,18 . O forte efeito de acoplamento spin-órbita no átomo de irídio é o responsável pela alta faixa de estados excitados, os quais incluem os tripletos.…”
Section: Diodos Emissores De Luz Orgânicos (Do Inglês Organic Light-unclassified